MISE-EN-SCENE ANALYSIS IN CONSTRUCTING THE MALE GAZE IN BIGBANG'S BAE BAE VIDEO CLIP (2015) (Cinematology: Journal Anthology of Film and Television Studies, 2026)
Bae Bae is a song by Big Bang in the Rap and Beat genre which was released on May 1, 2015. The music video raises the theme of sensuality and explores the relationship between love, desire, and vulnerability. The delivery of the concept in the music video is carried out with a detailed approach related to the visual and narrative elements, namely the mise en scene approach. Bordwell stated that mise en scene consists of four components, namely the setting, costume and make-up, lighting, and staging. Mise en scene not only functions to build the aesthetics of the film, but also plays a crucial role in shaping the gender narrative shown in an audiovisual work. One of the gender narratives is the male gaze theory by Laura Mulvey. Mulvey states that the male gaze is a sexual imbalance, in the form of a perspective in the media divided into the view of men as active and women as passive. The phenomenon of the male gaze is the condition of women being depicted with erotic influence so that they conform to what men want. The phenomenon of men as active parties and exploiting women as passive parties to satisfy sexual fantasies seen in the music video Bae Bae by Big Bang will be the focus of this research. In this analysis, the researcher will highlight how the male gaze is displayed explicitly and implicitly in the music video by using the mise en scène approach as a tool to understand and explore the existing visual elements.